Do international non-governmental organizations inhibit globalization? The case of capital account liberalization in developing countries. (March 2015) - Pinheiro, Diogo; Chwieroth, Jeffrey M.; Hicks, Alexander
Why do countries liberalize capital controls? The literature identifies a range of possible reasons. Yet, despite considerable advances, the impact of international non-governmental organizations has yet to be considered. In fact, surprisingly, systematic analysis of the role of international non-governmental organizations in the diffusion of economic openness, financial or otherwise, has not been pursued previously. We offer the first such analysis by advancing the idea of 'climatic mimesis, ' which refers to the cultural climate for policymaking that results from country ties to international non-governmental organizations. International non-governmental organizations shape capital account regulation by altering the cultural climate in a country such that liberalization becomes a more problematic policy choice. Our statistical analysis of data from developing countries reveals that international non-governmental organization ties inhibited liberalization, as did relatively high public debt and concentrated domestic banking sectors. The presence of an International Monetary Fund program and liberalization by economic competitors encouraged it. We suggest that these findings have important implications for understanding the potential for convergence and divergence in an era of globalization.